Composite substrate, surface acoustic wave element, and method for manufacturing the composite substrate

The composite substrate with a reflective layer of alternating impedance layers and a modified layer addresses elastic wave leakage and durability issues, ensuring effective wave confinement and high Q values.

JP7612721B2Active Publication Date: 2025-01-14NGK CORP
View PDF 15 Cites 0 Cited by

Patent Information

Application Number
JP2022579385
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-02-05
Filing Date
2021-12-24
Publication Date
2025-01-14
Estimated Expiration
2041-12-24

AI Technical Summary

Technical Problem

Existing composite substrates used in SAW filters face issues with elastic wave leakage from the piezoelectric layer and require improved durability during processing.

Method used

A composite substrate design featuring a piezoelectric layer with a reflective layer composed of alternating low and high impedance layers, including a modified layer with specific density and composition, enhances wave confinement and durability.

Benefits of technology

The design effectively confines elastic wave energy within the piezoelectric layer while providing excellent durability, reducing peeling and cracking during processing, and achieving high Q values.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007612721000002
    Figure 0007612721000002
  • Figure 0007612721000003
    Figure 0007612721000003
  • Figure 0007612721000004
    Figure 0007612721000004
Patent Text Reader

Abstract

The present invention provides a composite substrate which has excellent durability, while confining the energy of elastic waves in a piezoelectric layer. A composite substrate according to one embodiment of the present invention comprises a piezoelectric layer and a reflective layer that is arranged on the back surface of the piezoelectric layer, while comprising a low impedance layer containing silicon oxide and a high impedance layer; a modification layer is formed at an end of the back surface of the piezoelectric layer; and the low impedance layer has a density of 2.15 g / cm3 or more.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a composite substrate, a surface acoustic wave element, and a method for manufacturing a composite substrate. [Background technology]

[0002] In communication devices such as mobile phones, for example, filters that utilize surface acoustic waves (SAW filters) are used to extract electrical signals of any frequency. This SAW filter has a structure in which electrodes and the like are formed on a composite substrate having a piezoelectric layer (see, for example, Patent Document 1).

[0003] In recent years, in the field of information and communication devices, there has been a demand for communication in high frequency bands, and in the SAW filter, there are cases where elastic waves leak from the piezoelectric layer, while the composite substrate is also required to have durability (e.g., durability during processing). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2020-150488 A Summary of the Invention [Problem to be solved by the invention]

[0005] A primary object of the present invention is to provide a composite substrate that is excellent in durability while confining the energy of elastic waves in the piezoelectric layer. [Means for solving the problem]

[0006] A composite substrate according to an embodiment of the present invention includes a piezoelectric layer, a reflective layer disposed on a rear surface side of the piezoelectric layer and including a low impedance layer and a high impedance layer containing silicon oxide, a modified layer is formed at an end portion on the rear surface side of the piezoelectric layer, and the density of the low impedance layer is 2.15 g / cm 3 That's all. In one embodiment, the modified layer has a thickness of 0.3 nm or more. In one embodiment, the modified layer has a thickness of 4.5 nm or less. In one embodiment, the modified layer comprises an amorphous body. In one embodiment, the modified layer has a silicon atom content of less than 10 atom %. In one embodiment, the high impedance layer comprises at least one selected from the group consisting of hafnium oxide, tantalum oxide, zirconium oxide, and aluminum oxide. In one embodiment, the high impedance layer and the low impedance layer each have a thickness of 0.01 μm to 1 μm. In one embodiment, in the reflective layer, the high impedance layers and the low impedance layers are laminated alternately. In one embodiment, the composite substrate has a supporting substrate disposed on the rear surface side of the reflective layer. In one embodiment, the composite substrate includes a bonding layer disposed between the reflective layer and the support substrate. A surface acoustic wave element according to another embodiment of the present invention includes the above-described composite substrate.

[0007] According to another aspect of the present invention, there is provided a method for producing a composite substrate, the method comprising the steps of: forming a modified layer on an end portion of a first principal surface side of a piezoelectric substrate having first and second principal surfaces opposed to each other; 3 The method includes depositing the above-mentioned low impedance layer, and depositing a high impedance layer on the first main surface side of the piezoelectric substrate on which the low impedance layer has been deposited. In one embodiment, the modified layer has a thickness of 0.3 nm or more. In one embodiment, the modified layer has a thickness of 4.5 nm or less. In one embodiment, the manufacturing method further includes polishing a surface of a second main surface side of the piezoelectric substrate on which the low impedance layer and the high impedance layer are formed. Effect of the Invention

[0008] According to an embodiment of the present invention, a composite substrate having excellent durability can be provided, which has a piezoelectric layer (piezoelectric substrate) and a reflective layer including a low-impedance layer having a predetermined density, and by forming a modified layer at the end of the piezoelectric layer (piezoelectric substrate), it is possible to confine the energy of elastic waves in the piezoelectric layer. [Brief description of the drawings]

[0009] [Figure 1] 1 is a schematic cross-sectional view showing an outline of a configuration of a composite substrate according to one embodiment of the present invention. [Figure 2A] 1A to 1C are diagrams illustrating an example of a manufacturing process for a composite substrate according to one embodiment. [Figure 2B] This is a continuation of Figure 2A. [Figure 2C] This is a continuation of Figure 2B. [Figure 2D] This is a continuation of Figure 2C. [Figure 2E] This is a continuation of Figure 2D. [Diagram 3] 1 is a cross-sectional TEM image of the composite substrate (first silicon oxide layer) of Example 2. [Figure 4] 1 is a cross-sectional TEM image of the composite substrate (first silicon oxide layer) of Comparative Example 5. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.

[0011] A. Composite board FIG. 1 is a schematic cross-sectional view showing an outline of a composite substrate according to one embodiment of the present invention. The composite substrate 100 has a piezoelectric layer 10, a reflective layer 20, and a support substrate 30 in this order. A modified layer 14 is formed on the end of the piezoelectric layer 10 on the side where the reflective layer 20 is arranged. By forming such layers, a composite substrate with excellent durability can be obtained. The reflective layer 20 includes a high-impedance layer with a relatively high acoustic impedance and a low-impedance layer with a relatively low acoustic impedance. The reflective layer 20 is a laminate of a plurality of impedance layers, and for example, the low-impedance layer and the high-impedance layer are alternately laminated. In the illustrated example, the reflective layer 20 has, from the piezoelectric layer 10 side, a low-impedance layer 21, a high-impedance layer 22, a low-impedance layer 23, a high-impedance layer 24, a low-impedance layer 25, a high-impedance layer 26, a low-impedance layer 27, and a high-impedance layer 28 in this order. Of the layers of the reflective layer 20, the low-impedance layer 21 is arranged closest to the piezoelectric layer 10. By disposing the reflective layer 20 having such a laminated structure, it is possible to effectively confine the energy of the elastic wave to the piezoelectric layer 10 side. The low impedance layer disposed closest to the piezoelectric layer 10 side may be referred to as a first low impedance layer.

[0012] In the illustrated example, the reflective layer 20 is a laminate of four high impedance layers and four low impedance layers, totaling eight layers, but the number of impedance layers included in the reflective layer is not limited to this. Specifically, the reflective layer may include at least one high impedance layer and at least one low impedance layer having different acoustic impedances. Preferably, the reflective layer has a multilayer structure of four or more layers.

[0013] Although not shown, the composite substrate 100 may further include any layer. The types, functions, number, combination, arrangement, etc. of such layers may be appropriately set according to the purpose. For example, the composite substrate 100 may include a bonding layer disposed between the reflective layer 20 and the support substrate 30.

[0014] The composite substrate 100 may be manufactured in any suitable shape. In one embodiment, the composite substrate 100 may be manufactured in the form of a so-called wafer. The size of the composite substrate 100 may be appropriately set depending on the purpose. For example, the diameter of the wafer is 50 mm to 150 mm.

[0015] A-1. Piezoelectric layer Any suitable piezoelectric material may be used as the material constituting the piezoelectric layer. As the piezoelectric material, a single crystal having a composition of LiAO3 is preferably used. Here, A is one or more elements selected from the group consisting of niobium and tantalum. Specifically, LiAO3 may be lithium niobate (LiNbO3), lithium tantalate (LiTaO3), or a lithium niobate-lithium tantalate solid solution.

[0016] When the piezoelectric material is lithium tantalate, it is preferable to use a piezoelectric layer whose normal direction is rotated 123 to 133° (e.g., 128°) from the Y axis to the Z axis around the X axis, which is the propagation direction of the surface acoustic wave, from the viewpoint of reducing the propagation loss. When the piezoelectric material is lithium niobate, it is preferable to use a piezoelectric layer whose normal direction is rotated 96 to 114° (e.g., 110°) from the Y axis to the Z axis around the X axis, which is the propagation direction of the surface acoustic wave, from the viewpoint of reducing the propagation loss.

[0017] The thickness of the piezoelectric layer is, for example, not less than 0.2 μm and not more than 5 μm.

[0018] The modified layer is, for example, made of an amorphous material and contains the elements constituting the piezoelectric layer. As a specific example, when the piezoelectric layer is made of lithium tantalate, the modified layer contains tantalum (Ta) and oxygen (O). In one embodiment, the content of silicon atoms (Si) when the total of Ta, O, Si and Ar in the modified layer is taken as 100 atom%, may be less than 10 atom%, or may be 5 atom% or less. The composition of the modified layer can be determined by energy dispersive X-ray analysis (EDX).

[0019] The thickness of the modified layer is, for example, 0.3 nm or more, and preferably 0.5 nm or more. On the other hand, the thickness of the modified layer is, for example, 4.5 nm or less, and preferably 4 nm or less. With such a thickness, a higher Q value can be achieved.

[0020] A-2.Reflective layer As described above, the reflective layer includes a high-impedance layer and a low-impedance layer having different acoustic impedances. The acoustic impedance of the high-impedance layer is relatively higher than that of the low-impedance layer. Specifically, the acoustic impedance of the material constituting the high-impedance layer is higher than that of the material constituting the low-impedance layer.

[0021] The multiple high impedance layers included in the reflective layer may each have the same configuration (e.g., material, thickness) or may have different configurations. Similarly, the multiple low impedance layers included in the reflective layer may each have the same configuration (e.g., material, thickness, density) or may have different configurations.

[0022] Examples of materials constituting the high impedance layer include hafnium oxide, tantalum oxide, zirconium oxide, and aluminum oxide. Among these, hafnium oxide is preferably used. By using hafnium oxide, the energy of the elastic wave can be more effectively trapped on the piezoelectric layer side.

[0023] The high impedance layer has a thickness of, for example, 0.01 μm to 1 μm, preferably 20 nm to 500 nm, and more preferably 100 nm to 300 nm.

[0024] A representative example of the material constituting the low impedance layer is silicon oxide. In one embodiment, the content of silicon oxide in the low impedance layer is, for example, 97% by weight or more. The ratio of oxygen atoms to silicon atoms in the low impedance layer (O / Si) is, for example, 1.85 to 2.05. The composition of the low impedance layer can be confirmed by Rutherford backscattering spectrometry (RBS). In addition, when analyzing, a sample obtained by forming a low impedance layer on a suitable substrate under the same conditions can be used.

[0025] The low impedance layer has a thickness of, for example, 0.01 μm to 1 μm, preferably 20 nm to 500 nm, and more preferably 100 nm to 300 nm.

[0026] The density of the low impedance layer is 2.15 g / cm 3 That is all. The low impedance layer having such density can effectively confine the energy of the elastic wave to the piezoelectric layer side. Specifically, the low impedance layer having such density is a dense film, and the occurrence of structural defects such as voids (nanopores) can be suppressed. As a result, an excellent reflective layer can be obtained, and a high Q value can be achieved. In addition, a high Q value can be secured even in combination with a modified layer. Furthermore, the low impedance layer having such density can contribute to improving the adhesion with the piezoelectric layer. Specifically, in the deposition of the dense first low impedance layer, a modified layer is easily formed on the adjacent layer (substrate), and a composite substrate with excellent durability can be obtained. Generally, from the viewpoint of effectively confining the energy of the elastic wave to the piezoelectric layer side, it is considered desirable to form a low impedance layer with a low density and a low bulk modulus, but the combination of the low impedance layer having the above density and the modified layer can simultaneously achieve a high Q value and excellent durability, which is an unexpected and excellent effect.

[0027] The density of the low impedance layer is 2.2 g / cm 3 or more, 2.25 g / cm 3or more, 2.3 g / cm 3 or more. By having such a density, a composite substrate with excellent heat resistance can be obtained. For example, even when the composite substrate is subjected to processing in which heat of 200°C or more is applied, peeling in the composite substrate (specifically, peeling in the reflective layer) can be suppressed. Such peeling is thought to be caused by the active movement of moisture that has been taken into the impedance layer (representatively, in the void) due to heating. The density of the low impedance layer is, for example, 2.5 g / cm. 3 The following is the result.

[0028] It is sufficient that at least one low impedance layer (for example, the first low impedance layer) included in the reflective layer satisfies the above density, but it is preferable that all low impedance layers included in the reflective layer satisfy the above density.

[0029] The density of the impedance layer can be determined by X-ray reflectometry (XRR).

[0030] The impedance layer can be formed by any suitable method. For example, it can be formed by physical vapor deposition such as sputtering or ion beam assisted deposition (IAD), chemical vapor deposition, or atomic layer deposition (ALD). Preferably, IAD is used. By using IAD, a dense impedance layer can be formed, and the above density can be achieved satisfactorily. In addition, when forming the first low impedance layer, a modified layer can be formed satisfactorily on an adjacent layer (substrate). For example, a modified layer having a desired thickness can be formed.

[0031] A-3.Support board Any suitable substrate may be used as the support substrate 30. The support substrate may be made of a single crystal or a polycrystalline material. The material constituting the support substrate is preferably selected from the group consisting of silicon, sialon, sapphire, cordierite, mullite, glass, quartz, crystal, and alumina.

[0032] The silicon may be single crystal silicon, polycrystalline silicon, or high resistance silicon.

[0033] Typically, the sialon is a ceramic obtained by sintering a mixture of silicon nitride and alumina. For example, Si 6-w Al w O w N 8-w Specifically, sialon has a composition in which alumina is mixed into silicon nitride, and w in the formula indicates the mixing ratio of alumina. w is preferably 0.5 or more and 4.0 or less.

[0034] Typically, the sapphire is a single crystal having a composition of Al2O3, and the alumina is a polycrystalline body having a composition of Al2O3. The alumina is preferably translucent alumina.

[0035] Typically, the cordierite is a ceramic having a composition of 2MgO·2Al2O3·5SiO2, and the mullite is a ceramic having a composition in the range of 3Al2O3·2SiO2 to 2Al2O3·SiO2.

[0036] The thermal expansion coefficient of the material constituting the support substrate is preferably smaller than that of the material constituting the piezoelectric layer. Such a support substrate can suppress changes in the shape and size of the piezoelectric layer when the temperature changes, and can suppress changes in, for example, the frequency characteristics of the resulting surface acoustic wave element.

[0037] The thickness of the support substrate may be any appropriate thickness, and is, for example, 100 μm to 1000 μm.

[0038] A-4.Joining layer As described above, the composite substrate may have a bonding layer. Examples of materials constituting the bonding layer include silicon oxide, silicon, tantalum oxide, niobium oxide, aluminum oxide, titanium oxide, and hafnium oxide. The thickness of the bonding layer is, for example, 0.005 μm to 1 μm.

[0039] The bonding layer may be formed by any suitable method, specifically, by the same method as the method for forming the impedance layer.

[0040] A-5. Manufacturing method A method for manufacturing a composite substrate according to one embodiment of the present invention includes forming a modified layer at an end portion of a first main surface side of a piezoelectric substrate having first and second main surfaces opposing each other, depositing a low-impedance layer containing silicon oxide on the first main surface side of the piezoelectric substrate, and depositing a high-impedance layer on the first main surface side of the piezoelectric substrate on which the low-impedance layer is deposited.

[0041] Specifically, the composite substrate can be obtained by forming the modified layer on the piezoelectric substrate, sequentially depositing the impedance layer constituting the reflective layer, and directly bonding the piezoelectric substrate on which the reflective layer is formed to the support substrate. The thickness of the piezoelectric substrate is, for example, 200 μm or more and 1000 μm or less.

[0042] 2A to 2E are diagrams showing an example of a manufacturing process of a composite substrate according to one embodiment. FIG. 2A shows a state in which a modified layer 14 is formed on an end (upper end) of a first main surface side of a piezoelectric substrate 12 having a first main surface and a second main surface facing each other, and the formation of a first low-impedance layer 21 on the modified layer 14 is completed. The modified layer 14 is preferably a layer formed by modifying the upper end of the piezoelectric substrate 12. Such a modified layer is formed, for example, by evaporating a film-forming material of the first low-impedance layer 21 on the piezoelectric substrate 12 while applying energy (e.g., ion energy) to the film-forming material. Specifically, when the first low-impedance layer 21 is formed, atoms constituting the first low-impedance layer 21 are bombarded into the upper end of the piezoelectric substrate 12, and the modified layer 14 can be formed.

[0043] After the low-impedance layer 21 is formed, impedance layers 22-28 are sequentially formed on the low-impedance layer 21 to form the reflective layer 20, as shown in Fig. 2B. The impedance layers 21-28 may be formed by the same method and conditions, or may be formed by different methods and conditions.

[0044] 2C shows a state where the bonding layer 40 is formed on the reflective layer 20, and FIG. 2D shows a process of directly bonding the piezoelectric substrate 12 on which the reflective layer 20 and the bonding layer 40 are formed to the support substrate 30. In the direct bonding, it is preferable that the bonding surfaces are activated by any appropriate activation process. For example, the surface 40a of the bonding layer 40 is activated, and the surface 30a of the support substrate 30 is activated, and then the activated surface of the bonding layer 40 and the activated surface of the support substrate 30 are brought into contact with each other and pressed to be directly bonded. In this way, the composite substrate 110 shown in FIG. 2E is obtained.

[0045] The surface (lower surface) 12a on the second main surface side of the piezoelectric substrate 12 of the obtained composite substrate 110 is typically subjected to processing such as grinding and polishing so as to form a piezoelectric layer of the desired thickness. Due to the formation of the modified layer 14, the composite substrate 110 can have excellent durability. For example, the composite substrate 110 can have excellent durability during processing such as grinding and polishing. Specifically, the occurrence of peeling of the composite substrate (specifically, peeling near the boundary between the piezoelectric substrate 12 and the low impedance layer 21) due to processing such as grinding and polishing can be suppressed. As a result, a composite substrate of excellent quality without peeling can be obtained.

[0046] Preferably, the surface of each layer (specifically, the piezoelectric layer, the piezoelectric substrate, the reflective layer, the support substrate, and the bonding layer) is flat. Specifically, the arithmetic mean roughness Ra of the surface of each layer is preferably 1 nm or less, and more preferably 0.3 nm or less. Methods for flattening the surface of each layer include, for example, mirror polishing, lap polishing, and chemical mechanical polishing (CMP).

[0047] During the above film formation and bonding, it is preferable to clean the surface of each layer, for example, to remove abrasive residues, processing-degraded layers, etc. Examples of cleaning methods include wet cleaning, dry cleaning, and scrub cleaning. Among these, scrub cleaning is preferable because it can clean easily and efficiently. A specific example of scrub cleaning is a method in which a cleaning agent (e.g., Sun Wash series manufactured by Lion Corporation) is used, followed by cleaning with a scrub cleaner using a solvent (e.g., a mixed solution of acetone and isopropyl alcohol (IPA)).

[0048] The activation process is typically performed by irradiating a neutralizing beam. Preferably, a neutralizing beam is generated using an apparatus such as that described in JP 2014-086400 A, and the activation process is performed by irradiating the neutralizing beam. Specifically, a saddle field type fast atom beam source is used as the beam source, an inert gas such as argon or nitrogen is introduced into a chamber, and a high voltage is applied from a DC power source to the electrodes. As a result, a saddle field type electric field generated between the electrode (positive electrode) and the housing (negative electrode) moves electrons, and a beam of atoms and ions is generated by the inert gas. Of the beams that reach the grid, the ion beam is neutralized by the grid, and a beam of neutral atoms is emitted from the fast atom beam source. The voltage during the activation process by beam irradiation is preferably 0.5 kV to 2.0 kV, and the current during the activation process by beam irradiation is preferably 50 mA to 200 mA.

[0049] The contact and pressure application of the bonding surfaces is preferably carried out in a vacuum atmosphere. The temperature at this time is typically room temperature. Specifically, the temperature is preferably 20° C. or higher and 40° C. or lower, and more preferably 25° C. or higher and 30° C. or lower. The pressure applied is preferably 100N to 20,000N.

[0050] B. Surface acoustic wave element The surface acoustic wave element according to the present invention includes the composite substrate. The composite substrate can achieve a high Q value. In addition, since the composite substrate has excellent durability, for example, a surface acoustic wave element obtained by subjecting the composite substrate to processing such as forming electrodes and cutting can be prevented from peeling or cracking, and can have excellent quality. Such a surface acoustic wave element is suitably used as a SAW filter in communication devices such as mobile phones. EXAMPLES

[0051] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples.

[0052] [Example 1] A lithium tantalate (LT) substrate with an orientation flat (OF) portion, a diameter of 4 inches, and a thickness of 250 μm (a 128° Y-cut X-propagation LT substrate with the propagation direction of the surface acoustic wave (SAW) as X, and a cut-out angle of a rotated Y-cut plate) was prepared. The surface of this LT substrate was mirror-polished to an arithmetic mean roughness Ra of 0.3 nm. Here, the arithmetic mean roughness Ra was a value measured with an atomic force microscope (AFM) in a field of view of 10 μm × 10 μm.

[0053] Next, a first silicon oxide layer (thickness: 150 nm) was formed on the polished surface of the LT substrate by the IAD method. -2 The molten quartz was irradiated with an electron beam under a vacuum of 2×10 Pa, and a film was formed at a film formation rate of 1 nm / sec under a flow of oxygen and argon gas (flow ratio: oxygen / argon = 2.0). Then, a hafnium oxide layer (thickness: 200 nm) and a silicon oxide layer (thickness: 150 nm) were formed in sequence. -2 A hafnium oxide target or a silicon oxide target was irradiated with an electron beam under a pressure of 10 Pa, and a film was formed at a film formation rate of 0.5 nm / sec under a flow of oxygen and argon gas (flow ratio: oxygen / argon = 2.2). In this way, a reflective layer as shown in Figure 1 was formed.

[0054] Next, a silicon oxide layer (thickness: 80-190 nm, arithmetic mean roughness Ra: 0.2-0.6 nm) was formed on the reflective layer. Specifically, the film was formed by DC sputtering using a boron-doped Si target. In addition, oxygen gas was introduced as an oxygen source. At this time, the total pressure and oxygen partial pressure of the atmosphere in the chamber were adjusted by adjusting the amount of oxygen gas introduced. Thereafter, chemical mechanical polishing (CMP) was performed on the surface of the silicon oxide layer to form a bonding layer (thickness: 50 nm, arithmetic mean roughness Ra: 0.08-0.4 nm).

[0055] A support substrate made of silicon having an OF portion, a diameter of 4 inches, and a thickness of 500 μm was prepared. The surface of this support substrate was subjected to chemical mechanical polishing (CMP), and the arithmetic mean roughness Ra was 0.2 nm.

[0056] Next, the LT substrate and the support substrate were directly bonded to each other. Specifically, the surface of the LT substrate (the bonding layer side) and the surface of the support substrate were cleaned, and then both substrates were placed in a vacuum chamber and heated for 10 -6 After evacuation to the Pa range, the surfaces of both substrates were irradiated with a fast atomic beam (accelerating voltage 1 kV, Ar flow rate 27 sccm) for 120 seconds. After irradiation, the beam-irradiated surfaces of both substrates were overlapped and pressed with 10,000 N for 2 minutes to bond the two substrates. The resulting bonded body was then heated at 100°C for 20 hours.

[0057] Next, the rear surface of the LT substrate of the above bonded body (composite substrate) was ground and polished from the original thickness of 250 μm to 0.5 μm, thereby obtaining a composite substrate having a piezoelectric layer with a thickness of 0.5 μm.

[0058] [Examples 2 to 6 and Comparative Examples 1 to 5] A composite substrate was obtained in the same manner as in Example 1, except that the film formation conditions for the first silicon oxide layer (thickness: 150 nm) by the IAD method were changed.

[0059] <Evaluation> The composite substrate thus obtained was subjected to the following evaluations. The evaluation results are summarized in Table 1. 1. Check the modified layer The presence or absence of the formation of a modified layer on the LT substrate was confirmed by observation (TEM observation) using a field emission transmission electron microscope ("JEM-F200" manufactured by JEOL). The sample for TEM observation was prepared by the FIB method, and the acceleration voltage for TEM observation was 200 kV and the magnification was 5.4 million times. As an example, a cross-sectional TEM image of the composite substrate (first silicon oxide layer) of Example 2 is shown in FIG. 3, and a cross-sectional TEM image of the composite substrate (first silicon oxide layer) of Comparative Example 5 is shown in FIG. 4. When the modified layer was observed, its thickness was measured. Specifically, the modified layer was measured from the point where the crystal structure of the LT substrate was confirmed in the obtained TEM image to the point where the color (tone) of the silicon oxide layer was intermediate between the color of the modified layer, and the thickness was measured. The measurement point was the thickest point in the obtained TEM image. 2. Density Measurement The density was determined by X-ray reflectometry (XRR). The analysis was performed using a fully automated multipurpose X-ray diffraction device (Rigaku's "SmartLab") under the following conditions: incident X-ray wavelength 0.15418 nm (CuKα radiation), X-ray output 45 kV, 200 mA, measurement range (angle with the sample surface) 0.0 to 4.0°, and measurement step 0.01°. As a measurement sample, a silicon oxide layer was formed on a separate substrate (for example, a silicon substrate, a lithium niobate substrate, or a lithium tantalate substrate) under the same conditions. The obtained analytical model was divided into three parts, the substrate, the modified layer, and the silicon oxide layer, and the analysis was performed to determine the density of the silicon oxide layer. When the silicon oxide layer was thick or when it was difficult to analyze the thickness of the modified layer, the analytical model was divided into two parts, the substrate and the silicon oxide layer, and the density of the silicon oxide layer was determined from the critical angle of the measurement profile. 3. Q value measurement The frequency characteristics of the surface acoustic wave element obtained by forming a comb-shaped electrode on the surface of the piezoelectric layer of the composite substrate were measured using a network analyzer. The resonant frequency fr and its half-width Δfr were obtained from the frequency characteristics obtained, and the Q value was calculated by fr / Δfr. 4.Durability For each of the examples and comparative examples, the back surface of the LT substrate was observed under a microscope before and after grinding and polishing to check whether peeling occurred in the composite substrate, thereby evaluating durability.

[0060] [Table 1]

[0061] In Comparative Example 1 and Comparative Example 5, where no modified layer was observed, peeling was observed due to cutting and polishing of the back surface of the LT substrate. Specifically, peeling was observed near the boundary between the LT substrate and the first silicon oxide layer (at the beginning of the formation of the first silicon oxide layer on the LT substrate).

[0062] It can be seen that in each example, a high Q value can be obtained even in the presence of a modified layer.

[0063] When the modified layer was analyzed by energy dispersive X-ray analysis (EDX), Ta, O and a trace amount of Ar were detected. A measurement sample (a silicon oxide layer formed on an LT substrate) was prepared under the same conditions as in Example 2, and the composition of the modified layer was analyzed by STEM-EDX observation using an atomic resolution analytical electron microscope (JEOL, JEM-ARM200F Dual-X) and an energy dispersive X-ray analyzer (JEOL, JED-2300) at an acceleration voltage of 200 kV and a beam spot size of about 0.2 nmΦ. Specifically, a line analysis was performed in the thickness direction of the modified layer, and the analysis points were within a thickness range of 25% of the thickness of the modified layer from the center of the thickness direction of the modified layer to the first silicon oxide layer side and the LT substrate side, respectively, and the average value of the results measured at intervals of about 0.2 nm in the thickness direction was calculated. As a result, the content of Si was 7.0 atom% or less when the total of Ta, O, Si and Ar was 100 atom%. [Industrial Applicability]

[0064] A composite substrate according to an embodiment of the present invention can be suitably used for a surface acoustic wave element. [Explanation of symbols]

[0065] 10 Piezoelectric layer 14 Modification layer 20 reflective layer 21 Low impedance layer 22 High impedance layer 23 Low impedance layer 24 High impedance layer 25 Low impedance layer 26 High impedance layer 27 Low impedance layer 28 High impedance layer 30 Support substrate 40 Bonding layer 100 Composite Board 110 Composite Board

Claims

1. A piezoelectric layer; a reflective layer disposed on a rear surface side of the piezoelectric layer and including a low impedance layer and a high impedance layer including silicon oxide; A support substrate disposed on a rear surface side of the reflective layer; a bonding layer disposed between the reflective layer and the support substrate; A modified layer containing silicon atoms is formed at an end portion on the rear surface side of the piezoelectric layer, The density of the low impedance layer is 2.15 g / cm 3 That's all. The low impedance layer is in contact with the modified layer. Composite board.

2. The composite substrate according to claim 1 , wherein the modified layer has a thickness of 0.3 nm or more.

3. The composite substrate according to claim 1 , wherein the modified layer has a thickness of 4.5 nm or less.

4. The composite substrate according to claim 1 , wherein the modified layer comprises an amorphous body.

5. 5. The composite substrate according to claim 1, wherein the modified layer has a silicon atom content of less than 10 atom %.

6. 6. The composite substrate of claim 1, wherein the high impedance layer comprises at least one selected from the group consisting of hafnium oxide, tantalum oxide, zirconium oxide and aluminum oxide.

7. 7. The composite substrate according to claim 1, wherein the high impedance layer and the low impedance layer each have a thickness of 0.01 μm to 1 μm.

8. The composite substrate according to claim 1 , wherein the high impedance layers and the low impedance layers are alternately laminated in the reflective layer.

9. A composite substrate described in any one of claims 1 to 8, wherein the material constituting the bonding layer is selected from silicon oxide, silicon, tantalum oxide, niobium oxide, aluminum oxide, titanium oxide and hafnium oxide.

10. A surface acoustic wave element comprising the composite substrate according to claim 1 .

11. forming a modified layer on an end portion of a piezoelectric substrate having a first principal surface and a second principal surface opposed to each other, the end portion being on the first principal surface side; The first main surface of the piezoelectric substrate contains silicon oxide and has a density of 2.15 g / cm 3 Depositing the above low impedance layer; and forming a high-impedance layer on a first main surface side of the piezoelectric substrate on which the low-impedance layer is formed; Including, forming the modified layer by depositing the low impedance layer on the piezoelectric substrate; A method for manufacturing a composite substrate.

12. The method according to claim 11 , wherein the modified layer has a thickness of 0.3 nm or more.

13. The method according to claim 11 or 12, wherein the modified layer has a thickness of 4.5 nm or less.

14. The method according to claim 11 , further comprising polishing a surface of a second main surface side of the piezoelectric substrate on which the low impedance layer and the high impedance layer are formed.

Citation Information

Patent Citations

  • Resonance acoustic isolator for thin film acoustic resonator

    JP1997199978A

  • Thin film bulk acoustic resonator, method for producing same, filter, composite electronic component device, and communication apparatus

    JP2005110230A

  • Method of manufacturing piezoelectric vibrator

    JP2008178071A

  • Method for manufacturing insulator film

    JP2012227336A

  • Composite substrate, and method for manufacturing composite substrate

    JP2017139720A